Uma análise da geolocalização e gameficação para o desenvolvimento de aplicações móveis - Coelho, Rafael Cortat (2013)
Since Web 2.0 has been created, the users role has faced massive changes, leading to a type of user experience characterized by the content generation and collaboration. Supported by modern mobile devices powered with advanced functions, collaboration became a reality in several segments of society, which now takes advantage of the new opportunities brought by mobile applications. In this context, a strong demand for geolocalization feature can be observed, as the practice characterized by the interaction of groups that share even temporally the same geographical region continuously grows. Thereby, the triad SoLoMo (social, local, mobile) is inserted into the scenario and becomes the main topic of this research. In addition to this, we can detect the growth of the incorporation of game mechanics into digital environments, a characteristic called gamification , which derives from the word game . This enhancement is relevant since it is an artifice able to motivate users to interact more and better with the environment and with other users. Among the applications that exploit all these features, Foursquare, which is a social network that allows users to indicate where they are at a certain moment, deserves full attention. Thus, it s relevant for this research to include an analysis of this tool, given its importance to the market. Therefore, the purpose of this research, which has a descriptive exploratory methodology, is to evidence how this scenario affects and encourages the development of mobile applications. In order to accomplish this, the research was conducted based on the contributions of Pierre Levy, André Lemos and Lucia Santaella on collaboration, social networking and collective intelligence. Further, the contributions of Martha Gabriel, Rachel Rechuero and the duos Hugo Fuks & Mariano Pimentel and Gabe Zichermann & Christopher Cunningham on more specific topics complemented the theoretical foundation